Доля Франкових казок в англомовному світі - Максимів, Г. (Народна творчість та етнографія, 2008)
The main problems of the English translation of Ivan Franko's fairy-tales are explored in the article. A question is considered from point of three measurings of existence of the translated text: author's intention, intention of text and intention of translator. Reflected are main aspects, which it follows to take into account them to the translator during translation of fairy-tales, namely: recreation of character's chronotopos of the heroes; recreation of local chronotopos (proper names and geographical names); recreation of the ethnolinguistical component: a) pair formations of the lexical level (appendixes), b) realities, c) phraseology units, d) traditional fairy-tales formulae. From point of these aspects all existent English-language translations of I. Franko's fairy-tales are analysed.